Penerapan Joyful Learning 7 Jumps Strategy Untuk Meningkatkan Kompetensi Guru Sekolah Dasar - Erni, Erni; Azhar, Fadly; Aruan, Rumiri. R.; Dahnilsyah, Dahnilsyah; Novitri, Novitri; Prawati, Atni (Abdimas Indonesian Journal, 2024)
SDN 024 Teluk Binjai in Dumai City has implemented English lessons in its school curriculum. However, inadequate teacher competencies have been a factor in the low levels of students' communication skills and interactive mediation. Teachers need to apply active, creative, and contextual learning models to make the learning process enjoyable and foster social interaction between students and teachers. Joyful learning, combined with games, is prioritized to create active, creative, and contextual learning. Based on these challenges, a training program on the implementation of the Joyful Learning 7Jumps Strategy research results was conducted for 12 teachers teaching English at SDN 024 Teluk Binjai, Dumai. The training methods included technical guidance and workshops on designing lessons, student worksheets, and assessments, followed by peer teaching practice. The program was conducted offline in August 2024 and continued with online mentoring and supervision. The training was deemed successful, with teachers’ knowledge and readiness to implement the Joyful Learning 7Jumps Strategy scoring an average of 3.82, categorized as high, and the teaching modules were applicable for teachers. The community service activity effectively enhanced teachers’ competencies in implementing the strategy creatively, innovatively, and contextually, directly improving the quality of English teaching at SDN 024 in Dumai City. The limitation of the training lies in the unknown effectiveness of the model and product in improving students’ English proficiency.